Soil-Landscape Relationship in the Northern Volcanic Mountain of Leyte, Philippines - Rallos, Roland V.; Asio, Victor B.; Villamayor, Faustino P. (Annals of Tropical Research, 2017)
Studies on soil-landscape relationships are necessary to improve our understanding of the spatial distribution and variation of soils for their sustainable management. This study evaluated the relationship between soil properties and landscape position in the northern volcanic mountain of Leyte, Philippines. Five soil profiles located on summit, shoulder, backslope and footslope positions were evaluated. Findings revealed that the degree of soil development as well as the soil morphophysical and chemical properties varied with landscape position. The soil in the most stable position (summit) had thicker solum and slightly more developed soil profile than the soils in other landscape positions. On the other hand, soils in the unstable position (backslope) generally had thinner solum. All the five soils also revealed the influence of the andesitic volcanic parent material on their properties. They all showed some properties typical of Andisols such as low bulk density and high pH in NaF although they were classified as Andic Dystrudept. The soils all possessed physical and chemical constraints for crop production.